SUNBATHING FOR IMPROVING THE SLEEP QUALITY OF THE ELDERLY - Ninuk, Devin Prihar; Wijanarko, Arif; Nasrudin, Nasrudin (Nurse and Holistic Care, 2022)
Background: Sleep changes is associated with the aging process. The elderly reported that they often had difficulty in falling and staying asleep Objective: This study purposed to determine the effect of sunbathing on improving the elderly’s sleep quality in Werda Nursing Home. Methods: A quasi-experimental was conducted with one group pre-post-test design. The population was 42 elderly in Werda Nursing Home. The sample was 38 respondents taken by quota sampling technique. The modified PSQI was used to collect data. Statistical analysis was using Mann Whitney showed a p-value of 0,000 smaller than α 0.05. Result: The study results showed that frequency of pre-test data before treatment obtained a mean of 7.06, in the post-test after being given treatment for 2 weeks, the mean obtained was 4.04. Conclusion: Sunbathing affected the elderly’s sleep quality. The sunlight had a double impact in enhancing melatonin through the retinohypothalamic duct and SCN and stimulating the nocturnal melatonin phase by rearranging the pacemaker.